The Influence of Learning Motivation on Increasing Student Learning Achievement - Miranti Entahna Anugeraya; Fatima Az-zahra; Reski Ramadhani; M. Iqbal Andriyano (Journal of Psychology and Social Sciences, 2024)
This study aims to determine whether there is an Effect between Learning Motivation on Increasing Learning Achievement of Islamic Psychology Students in Semester 4 of Raden Fatah State Islamic University Palembang. This study used a quantitative approach with a comparative causal method with data analysis using a simple linear regression test. The subjects of this study were N = 30 4th semester psychology students. Data collection techniques using questionnaire techniques. Variable data on The Effect of Learning Motivation on Increasing Learning Achievement of Psychology Students in Semester 4 of Raden Fatah State Islamic University Palembang was obtained through a controlling scale, expressing learning motivation and increasing learning achievement with 20 statement items. The significant value in the data in the form of 0.000 means it is lower than the significant level of 0.05, which can be concluded that the learning motivation variable has an influence on the learning achievement improvement variable.